Studying the orientation of values towards individualism or collectivism through the structural and attitudinal approach of social representation of individuality and collectivity in a Greek and a French sample - Σακαλάκη Μαρία (Psychology: the Journal of the Hellenic Psychological Society, 2020)
This study focuses on social representations about the constructs of individuality and collectivity in two European capitals. The structure as well as the attitudinal dimension of social representations was explored through a material collected by the method of free associations and analyzed by the structural approach proposed by P. Vergès. Participants (68 Psychology students from the University of Paris 5 and 109 Psychology students from Panteion University) filled out a questionnaire. Based on the examination of previous studies, we hypothesized that the Greek sample would produce more positive associations and more positive evaluation of the terms associated to collectivity than the French sample and that the French sample would produce more positive associations and a more positive evaluation of the terms associated to individuality. The structure of social representations for the two samples should also confirm these differences, highlighting through the central and peripheral elements of the representations that the Greek sample favors collectivism compared to the French sample and inversely that the French sample favors individuality compared to the Greek sample. The findings confirm our hypotheses.